The Contribution of Red Onion Farming to Farmers’ Income in Tampabulu Village, North Poleang Subdistrict, Bombana Regency - Anisah; Bafadal, Azhar; Fyka, Samsul Alam (International journal of technology and education research, 2026)
This research was motivated by the challenges faced by shallot farming in Tampabulu Village, North Poleang District. These challenges include a longer cultivation time and increased labor costs due to seeding, transplanting, and preventing Fusarium wilt during the rainy season. These factors influence productivity and income, prompting farmers to seek income sources other than shallots. Based on these conditions, this study aims to analyze the contribution of shallot farming to farmers' incomes, the extent to which these farms support their economic needs, and their relative importance compared to other sources of income. The research location was purposively selected based on the consideration that Tampabulu Village relies on shallot farming as its primary source of income. The number of respondents in this study was 12 shallot farmers. Data analysis used income analysis and farm income contribution. The results showed that shallot farming requires production costs of Rp21.107.472 per planting season, with income obtained of Rp115.017.528 per season. Income from shallot farming provides a high contribution to the total income of farmers by 82 %, which means that shallot farming is one of the main sources in supporting the economic needs of farmers in Tampabulu Village